Supervised Learning Techniques for Identifying Credit Fraud - Maduskar, Advait; Ladukar, Aniket; Gore, Shubhankar (International Journal of Computer Sciences and Engineering, 2019)
Credit fraud is a broad term associated with theft or fraudulent transactions that involve the usage of a credit card. The fraud detection systems today are only capable of preventing one-twelfth of one percent of all transactions processed, which still results in huge losses. To the human eye, fraudulent transactions are indistinguishable from real ones. However, there are underlying patterns common to these transactions that can be recognized by machine learning algorithms. In this paper, we have trained supervised learning models on a dataset containing more than 280,000 transactions. We go on to evaluate the performance of each of these models on the dataset in terms of accuracy and precision and compare them with each other. With this, we show that the Random Forest model shows promising results for identifying credit fraud when trained on a labelled dataset.